2019
DOI: 10.2340/00015555-3298
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Local Increase of Granulysin Expression in Cytotoxic Lymphocytes in Severe Psoriasis

Abstract: SIGNIFICANCEPsoriasis is a chronic skin disease that affects 2% of the population. Apart from skin symptoms, patients may have psoriatic arthritis and other comorbidities, which can result in grave functional and emotional consequences. Finding a reason for psoriatic plaque formation is the major goal in recent psoriasis investigations. We demonstrated a possible involvement of cytotoxic molecule granulysin in psoriasis pathogenesis. Granulysin is highly expressed in peripheral blood and skin lesions of psoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
(34 reference statements)
1
17
0
1
Order By: Relevance
“…The frequency of GNLY + NK cells is increased in the peripheral blood of psoriasis patients. Similarly, the frequency of psoriatic lesion GNLY + NK cells is increased relative to healthy controls and healthy non-psoriatic skin [102]. Interestingly, genetic analyses suggest a relationship between GNLY polymorphisms and psoriasis [103].…”
Section: Cytotoxic Function Of Nk Cells In Psoriasismentioning
confidence: 97%
“…The frequency of GNLY + NK cells is increased in the peripheral blood of psoriasis patients. Similarly, the frequency of psoriatic lesion GNLY + NK cells is increased relative to healthy controls and healthy non-psoriatic skin [102]. Interestingly, genetic analyses suggest a relationship between GNLY polymorphisms and psoriasis [103].…”
Section: Cytotoxic Function Of Nk Cells In Psoriasismentioning
confidence: 97%
“…Granulysin is a cytolytic antimicrobial peptide, and secreted with perforin and granzyme by NK and CD8 + T cells. The studies indicated increased granulysin positive cells in lesions and peripheral blood of patients and there is a link between granulysin and severe patients (315,322). Ermis et al showed that Granulysin rs7908 CC genotype and C allele had a protective effect against psoriasis and decreased the disease severity (322).…”
Section: Psoriasismentioning
confidence: 99%
“…Psoriasis is a relapsing and remitting, chronic inflammatory disease of skin, which is affecting almost 2% of the world's population (314,315). Psoriasis is a multifactorial disease in which genetic and environmental factors play a role in the pathogenesis but the etiopathology of the disease has not been fully clarified yet.…”
Section: Psoriasismentioning
confidence: 99%
“…Programmed cell death or apoptosis may be accomplished by nonsecretory mechanisms, through the interaction of effector and target cell membrane molecules, such as FasL-Fas, or by secretory mechanisms, mediated by degranulation and exocytosis of cytotoxic molecules from the cytotoxic cells’ cytoplasmatic granules, such as perforin, granzymes, and granulysin [ 52 , 53 ]. Previous studies have demonstrated increased granzyme B, perforin, and granulysin levels in lesional skin and peripheral blood of patients with psoriasis [ 54 , 55 , 56 , 57 , 58 ]. T lymphocytes’ subpopulations also have functional flexibility, converting Th17 and Treg to Th1 or Tc17 to Tc1 subpopulation [ 50 ].…”
Section: Immunopathogenesis Of Psoriasismentioning
confidence: 99%